Britain and the Cold War, 1945-1955 - Deighton, A (Cambridge University Press, 2010)
‘Britain and the Cold War, 1945-1955’, for the Cambridge History of the Cold War, eds Melvyn Leffler and Arne Westad, CUP, 2010, 112-133